Composite 5-methylations of cytosines modulate i-motif stability in a sequence-specific manner: Implications for DNA nanotechnology and epigenetic regulation of plant telomeric DNA - Školáková, Petra; Badri, Zahra; Foldynová-Trantírková, Silvie; Ryneš, Jan; Šponer, Jiří; Fojtová, Miloslava; Fajkus, Jiří; Marek, Radek; Vorlíčková, Michaela; Mergny, Jean-Louis; Trantírek, Lukáš (Biochimica et biophysica acta. General subjects, 2020)
The i-motif is a tetrameric DNA structure based on the formation of hemiprotonated cytosine-cytosine (C+.C) base pairs. i-motifs are widely used in nanotechnology. In biological systems, i-motifs are involved in gene regulation and in control of genome integrity. In vivo, the i-motif forming sequences are subjects of epigenetic modifications, particularly 5-cytosine methylation. In plants, natively occurring methylation patterns lead to a complex network of C+.C, 5mC+.C and 5mC+.5mC base-pairs in the i-motif stem. The impact of complex methylation patterns (CMPs) on i-motif formation propensity is currently unknown. We employed CD and UV-absorption spectroscopies, native PAGE, thermal denaturation and quantum-chemical calculations to analyse the effects of native, native-like, and non-native CMPs in the i-motif stem on the i-motif stability and pKa. CMPs have strong influence on i-motif stability and pKa and influence these parameters in sequence-specific manner. In contrast to a general belief, i) CMPs do not invariably stabilize the i-motif, and ii) when the CMPs do stabilize the i-motif, the extent of the stabilization depends (in a complex manner) on the number and pattern of symmetric 5mC+.5mC or asymmetric 5mC+.C base pairs in the i-motif stem. CMPs can be effectively used to fine-tune i-motif properties. Our data support the notion of epigenetic modifications as a plausible control mechanism of i-motif formation in vivo. Our results have implications in epigenetic regulation of telomeric DNA in plants and highlight the potential and limitations of engineered patterning of cytosine methylations on the i-motif scaffold in nanotechnological applications. •Complex methylation patterns impact i-motif stability in sequence dependent manner•Complex methylation patterns do not invariably stabilize DNA i-motif•In i-motif, methylation has a larger influence on stacking than base-paring